Serum Bilirubin in the Czech Population - Relationship to the Risk of Myocardial Infarction in Males - Eremiasova, Lenka; Hubacek, Jaroslav A; Danzig, Vilém; Adamkova, Věra; Mrazova, Lenka; Pitha, Jan; Lanska, Věra; Cífková, Renata; Vitek, Libor (Circulation journal, 2020)
BACKGROUND: The potential antiatherogenic role of bilirubin is generally acknowledged, so the aim of this study was to determine serum bilirubin concentrations and the prevalence of Gilbert syndrome (GS) in the Czech general population with particular reference to its relationship to the risk of myocardial infarction (MI). METHODS AND RESULTS: Biochemical markers were analyzed in 2 independent Czech post-MONICA studies (in total, n=3,311), and in 741 male MI patients. TheUGT1A1promoter gene variant (rs81753472) was analyzed in these MI patients and in the first control population cohort (n=717). Medians of serum bilirubin concentrations in the 2 Czech general population cohorts were 9.6 and 9.8 μmol/L (10.7 and 11.3 μmol/L in males, and 8.3 and 8.8 μmol/L in females; P<0.01). The prevalence of GS was 8.9%, twice as high in males compared with females (11.6 vs. 6.1%; P<0.01). TheUGT1A1(TA)7/7promoter repeats significantly influenced serum bilirubin concentrations in the controls, but not in the MI patients. Serum bilirubin concentrations were significantly lower in MI patients (7.7 vs. 10.7 μmol/L; P<0.01), with almost 5-fold lower prevalence of GS. CONCLUSIONS: Serum bilirubin concentrations and the prevalence of GS were determined in the Czech general population. Significantly lower serum bilirubin concentrations were observed in male MI patients.
Keywords: Cross-Sectional Studies; UGT1A1 promoter gene variants; Gilbertova nemoc; glukuronosyltransferasa; Male; retrospektivní studie; Risk Factors; Genotype; polymorfismus genetický; sexuální faktory; Česká republika; Adult; prevalence; Bilirubin; Myocardial infarction; Prospective Studies; bilirubin; dospělí; mužské pohlaví; promotorové oblasti (genetika); Polymorphism, Genetic; infarkt myokardu; Czech Republic; lidé; ženské pohlaví; Humans; Gilbert Disease; Sex Factors; Cardiovascular diseases; Myocardial Infarction; Promoter Regions, Genetic; rizikové faktory; průřezové studie; Prevalence; Gilbert syndrome; genotyp; Retrospective Studies; Glucuronosyltransferase; Female; lidé středního věku; Middle Aged; prospektivní studie